AT3 (Acyltransferase) Gene Isolated From Capsicum frutescens cv. Cakra Hijau - Habibi, Mohamad; Manggabarani, Andi Madhihah; Sulasmi, Eko Sri; Listyorini, Dwi (Journal of Tropical Life Science, 2013)
Chili pepper is widely used and cultivated by Indonesian people. There are three species of chili pepper, i.e.: Capsicum annuum L., Capsicum frutescens L., and Capsicum violaceum HBK. Capsicum frutescens L. has a higher economic value due to its pungency and carotenoid content. C. frutescens has several cultivars, one of those is Capsicum frutescens cv. Cakra Hijau. This cultivar is resistant against pest and disease and has very high pungency. This special character of chili pepper is born by its secondary metabolic, Capsaicin. Moreover, capsaicin also serves as defense mechanism, antiarthritis, analgesic, and anticancer. This study aimed to isolate Acyltransferase (AT3) gene which encoding Capsaicin Synthase (CS) enzyme. AT3 gene was isolated through PCR using forward primer 5-ATG GCT TTT GCA TTA CCA TCA-3 and reverse primer 5-CCT TCA CAA TTA TTC GCC CA-3. Data were analyzed using DNA Baser, BLAST, and ClustalX. This study has successfully isolated 404 bp fragments of AT3 gene. This fragments located at 1918-1434 bp referred to AT3 gene from Capsicum frutescens cv. Shuanla. Isolation of upstream and downstream fragments of AT3 gene from Capsicum frutescens cv. Cakra Hijau is undergoing.